The Role of Small and Medium Enterprises in Global Processes - Urbonavičius, Sigitas; Ivanauskas, Robertas (Ekonomika, 2002)
The main goal of this article is to review ways how small and medium enterprises (SME’s) can participate in global processes, and how they can benefit from this participation for their own development. It is widely recognised that SME’s are important players in every economy. On the other band, trends of economy globalisation are getting stronger and stronger. Participation and role of SME’s in globalisation remains rather unclear, since these companies have very limited resources and can not develop independent global strategies. The article argues that SME’s have a specific way of participating in global strategies, and it goes through participation in supply chains of global companies. In addition to direct business benefits, this participation triggers improvements in SME’s overall business practices. More than that, supply chain participation encourages usage of business consulting services, which historically is not very typical for SME’s of Baltic countries. The article provides some preliminary evidence of usage of specific types of consulting services that is triggered by participation of SME’s in global supply chains.